Ethics, leadership and biblical worldview against the naturalistic worldview - Turpo, Joel Ricardo (2012)
The author explores the relationship between worldview and ethics, and thenanalyzes the differences and ethical implications between the biblical worldviewand naturalist. In doing that, he studies the concept of man, his conscience, his discernmentof the laws, their perception of time and its difference with animals. Thepurpose is to show that both, the naturalistic worldview and the biblical worldview,ethical impact, consistent or inconsistent, in all categories of human existence andthe continuum of history.